Microbial communities in dark oligotrophic volcanic ice cave ecosystems of Mt. Erebus, Antarctica - Tebo, Bradley M.; Davis, Richard E.; Anitori, Roberto P.; Connell, Laurie B.; Schiffman, Peter; Staudigel, Hubert (Frontiers in Microbiology, 2015)
The Earth’s crust hosts a subsurface, dark, and oligotrophic biosphere that is poorly understood in terms of the energy supporting its biomass production and impact on food webs at the Earth’s surface. Dark oligotrophic volcanic ecosystems (DOVEs) are good environments for investigations of life in the absence of sunlight as they are poor in organics, rich in chemical reactants and well known for chemical exchange with Earth’s surface systems. Ice caves near the summit of Mt. Erebus (Antarctica) offer DOVEs in a polar alpine environment that is starved in organics and with oxygenated hydrothermal circulation in highly reducing host rock. We surveyed the microbial communities using PCR, cloning, sequencing and analysis of the small subunit (16S) ribosomal and Ribulose-1,5-bisphosphate Carboxylase/Oxygenase (RubisCO) genes in sediment samples from three different caves, two that are completely dark and one that receives snow-filtered sunlight seasonally. The microbial communities in all three caves are composed primarily of Bacteria and fungi; Archaea were not detected. The bacterial communities from these ice caves display low phylogenetic diversity, but with a remarkable diversity of RubisCO genes including new deeply branching Form I clades, implicating the Calvin-Benson-Bassham cycle as a pathway of CO2 fixation. The microbial communities in one of the dark caves, Warren Cave, which has a remarkably low phylogenetic diversity, were analyzed in more detail to gain a possible perspective on the energetic basis of the microbial ecosystem in the cave. Atmospheric carbon (CO2 and CO), including from volcanic emissions, likely supplies carbon and/or some of the energy requirements of chemoautotrophic microbial communities in Warren Cave and probably other Mt. Erebus ice caves. Our work casts a first glimpse at Mt. Erebus ice caves as natural laboratories for exploring carbon, energy and nutrient sources in the subsurface biosphere and the nutritional limits on life.